2017
DOI: 10.1080/14786419.2017.1360879
|View full text |Cite
|
Sign up to set email alerts
|

Acute and sub-acute toxicological evaluation of the alcoholic leaf and root extracts of Clerodendrum infortunatum L.

Abstract: Leaf and root extracts of Clerodendrum infortunatum L. have been reported to show anthelmintic efficacy on a cestode parasite Raillietina tetragona. Its leaf showed no toxicity at 1000 mg/kg body weight but root toxicity study was not known. Therefore, our study is to test both leaf and root extracts at 2000 and 3000 mg/kg body weight concentration given orally for 15 days in four groups of Swiss albino mice, keeping another set as control (without plant extract). Weight and behaviour of mice were recorded dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…This result indicates that CuAE did not interfere with the immune system. A normal hematological profile of animals treated chronically with C. inerme leaves ethyl acetate, chloroform, ethanolic, and aqueous extracts of C. infortunatum leaves and roots alcoholic extracts was also reported in the literature [14,15,17].…”
Section: Test Groups Satellite Groupsmentioning
confidence: 71%
See 2 more Smart Citations
“…This result indicates that CuAE did not interfere with the immune system. A normal hematological profile of animals treated chronically with C. inerme leaves ethyl acetate, chloroform, ethanolic, and aqueous extracts of C. infortunatum leaves and roots alcoholic extracts was also reported in the literature [14,15,17].…”
Section: Test Groups Satellite Groupsmentioning
confidence: 71%
“…This resulted in classifying CuAE in the category five of relatively non-toxic substances according to the GHS for the classification of chemicals [9]. A comparison between the oral LD 50 of CuAE and that of others species of Clerodendrum as C. infortunatum leaves methanolic extract (>2,000 mg/kg) [14], C. inerme leaves ethyl acetate, chloroform, ethanolic, and aqueous extracts (>3,000 mg/kg) [15], C. capitatum leaves hydroethanolic extract (>5,000 mg/kg) [16], and C. infortunatum leaves and roots alcoholic extracts (>3,000 mg/kg) [17] demonstrated that some species of this genus are relatively non-toxic and safe, and are therefore classified in category five according to the GHS. However, the oral LD 50 of CuAE was greater than the LD 50 of C. myricoides root aqueous extract (1,134 mg/kg), which belongs to category four of low toxic substances [18].…”
Section: Test Groups Satellite Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethanol extract of leaf and aqueous acetone extract of the root bark prepared from the Indian species of this plant have shown anti-inflammatory activity by inhibiting paw edema in rats ( Chandrashekar and Rao, 2013 ; Helen et al, 2018 ), whereas hydroethanolic extract of the leaf, stem, and root of C. infortunatum dose-dependently inhibited NO production in LPS-stimulated macrophage and showed no sign of mortality in the acute toxicity study ( Dutta et al, 2018 ). In another study, both leaf and root extracts were found safe in the in vivo experimental model ( Nandi et al, 2017 ). Several compounds have been identified from C. infortunatum with important medicinal values ( Nandi and Mawkhlieng Lyndem, 2016 ), the major being 3-deoxy-d-mannoic lactone, glycerin, and xylitol as analyzed using the gas chromatography coupled with mass spectroscopy (GC-MS) technique ( Ghosh et al, 2015 ) along with viscosene and several flavonoid glycosides ( Uddin et al, 2020 ).…”
Section: Resultsmentioning
confidence: 98%